Long-term outcomes of ischemic post-conditioning primary PCI and conventional primary PCI in acute STEMI: a meta-analysis of randomized trials. (3rd July 2021) - Mir, Tanveer; Uddin, Mohammed; Changal, Khalid Hamid; Perveiz, Eskara; Kaur, Jasmeet; Sattar, Yasar; Ullah, Waqas; Sheikh, Mujeeb
ABSTRACT: Background: Data regarding ischemic postconditioning during percutaneous coronary intervention (PCI) as compared conventional PCI alone has yielded conflicting results. Methods: Online databases comparing use of ischemic postconditioning percutaneous coronary intervention (ICP-PPCI) in STEMI patients with conventional PPCI were selected. Mortality, heart failure (HF), myocardial infarction (MI), and major adverse cardiac events (MACE) were evaluated. The primary outcome was composite of HF, MI, and mortality. Pooled risk ratio (RR) with 95% confidence interval (CI) were computed using random-effects model. Results: Eight studies consisting of 2, 566 patients (ICP-PPCI n = 1, 228; PPCI n = 1, 278) were included. The mean age for PPCI group was 61.38 ± 7.86 years (51% men) and for PCI 59.83 ± 8.94 years (47% men). There were no differences in outcome between ICP-PPCI and PPCI in terms of HF (RR 0.87 95% CI0.51–1.48; p = 0.29), MI (RR 1.28, 95%CI0.74–2.20; p = 0.20), mortality (RR 0.93, 95%CI0.64–1.34; p = 0.58), and MACE (RR 0.89, 95%CI0.74–1.07; p = 0.22). The results for composite event for the ICP-PPCI and PPIC procedures, at ≥1 year follow-up duration, were comparable (RR 1.00 95%CI0.82–1.22; p = 1). Conclusion: Ischemic postconditioning post percutaneous coronary intervention in STEMI patients has no long-term benefits over conventional PCI.